Response diversity and traits related to pepper yellow leaf curl disease resilience for resistant plants selection - TRI WAHONO DYAH AYU SAYEKTI; MUHAMAD SYUKUR; SRI HENDRASTUTI HIDAYAT; AWANG MAHARIJAYA; SOBIR SOBIR (Society for Indonesian Biodiversity, 2023)
Abstract. Sayekti TWDA, Syukur M, Hidayat SH, Maharijaya A, Sobir. 2023. Response diversity and traits related to pepper yellow leaf curl disease resilience for resistant plants selection. Biodiversitas 24: 5057-5064. Many chili species (Capsicum spp.) have been used and consumed, among them five species, namely Capsicum annuum, C. frutescens, C. chinense, C. baccatum and C. pubescens, are widely used. Most of these varieties are susceptible to Pepper Yellow Leaf Curl Disease (PYLCD) caused by Pepper yellow leaf curl virus (PYLCV) (Begomovirus, Geminiviridae). To control PYLCD, it is essential to gather resistant plant varieties to effectively shield cultivated plants from viral infections. An effective selection activity related to the target character is needed to get highly productive resistant plants. The objective of this study was to evaluate the relationship between resistance characters to crop production and to obtain appropriate selection criteria to increase the effectiveness of selecting resistant plants with good production. This study was conducted at Cikabayan Field, IPB University, Bogor, Indonesia. Twenty-nine genotypes of chili pepper were used, which consists of four species, including C. annuum, C. frutescens, C. chinense, and C. baccatum, arranged in a nested block design with three replications. The observed symptoms were yellowing of leaves followed by leaf malformations, but there were differences in the yellowing symptoms. From observation on visual symptoms, resistance characteristics, plant performance and productivity, there were differences in the response of each species to PYLCV attack. Correlation and path analysis results show that there was also differences in performance drop between C. annuum species and the non-C. annuum group. In C. frutescens, C. chinense, and C. baccatum, direct selection on resistance characters was able to increase the resistance level of selected plants while maintaining good crop production. Whereas for C. annuum species, the plant resistance level was not correlate with productivity reduction, so in the selection process, the percentage of yield decline needs to be considered to obtain resistant plants and maintain crop production.